Better housing for South Africa? - Hauptfleisch, Dries (Acta Structilia, 2001)
This article outlines the elements of the housing policy ·and programme strategies in South Africa, which has adopted a market-centred housing policy. The successes and failures (as well as the strengths and weaknesses) of the process are highlighted, indicating areas of concern and possible re-alignment and improvement for sustainability. Minimum specifications regarding services and buildings, including sizes (categories), must be provided in order to eliminate counter-productive perspectives from various platforms. One of the foremost socioeconomic problems in South Africa is the unemployment crisis. The solution lies in fighting poverty and providing sustainable housing. To subsidise low-income housing without subsidising local authorities for an extended period, will eventually lead to a new round of poverty in South Africa, and the subsequent collapse of local authorities. We cannot afford to solve an existing problem by creating a new one for the next millennium.